Acceptability Innovation of Low Poultry Egg Abon (EBELABON) with Addition Roasted Shallots for Overweight Z Generation - Febriyadin, Fitsyal; Lestari, Anik; Anantanyu, Sapja (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Being overweight due to lifestyle and dietary habits may lead to non-communicable diseases such as heart disease, stroke, and diabetes in the future. Generation Z is the generation born in 1995-2010. Use of shallots has antiobesity effects because it can reduce body fat and body weight Methods: The poultry eggs used in the acceptability of shredded are chicken eggs and this study was conducted by 25 moderately trained panelists with hedonic quality test. Data processing using Kruskall Wallis test to determine the real difference of ebelabon (egg shredded level delicious) with the addition of roasted onions 0%, 5%, 10% and 15% of the total poultry egg shredded served, shredded Data processing and analysis using SPSS software and presented in the form of tables, graphs, and narrative text. Results: The results showed that there was no significant difference in the acceptability of shredded poultry eggs. Based on the results of statistical analysis of four parameters on moderately trained panelists that the most preferred taste and overall were in formula 4, namely the addition of roasted onions 15% of the total shredded poultry eggs. Conclusion: As for the selected formula, formula 4 will be further tested by testing the content of macronutrients such as calories (energy), protein, fat and carbohydrates and carried out interventions for overweight students or generation Z who are currently studying.